Content-analysis of the native media - Kanzatova, А.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The scientific article analyzes the meaning and purpose of media monitoring, its role in the measurement of information security. The article considers the results of media monitoring, methods and stages of media monitoring, sources that are necessary for monitoring. Currently, a scientific analysis of the importance of monitoring of the media for the economy and business and its role in the development of these sectors. The system of automation of media monitoring in our country and the system of integrated work are analyzed differently on the basis of specific laws, as well as the purpose and tasks of monitoring the media under Soviet rule. The article also addresses the issues of censorship of modern Soviet media monitoring and modern areas of media monitoring, new technologies and methods used in it.